The effect of cutting direction and water based varnish type on sound absorption coefficient in some native wood species - Muslu, Mustafa Selmani (Maderas. Ciencia y Tecnología, 2024)
Noise which could be defined as disturbing sound, is becoming a major problem depending with developing technology. Controlling the noise helps raising the quality of life to higher levels. Although the intensity of the noise is not at a level that will affect human health, it should be reduced or eliminated, for better life standart. Due to the adverse effects of the noise level on health; the acoustic properties of living areas require serious consideration. Sound absorption coefficients of the materials used in the interior play an important role in providing sensory comfort depending on the volume. Natural and artificial wood are commonly used materials in interior design, especially in the construction of partition elements. In addition, wood is natural material and it has some important advantages and disadvantages. In this study the sound absorption coefficients of eastern beech and scotch pine trees, which are the most preferred materials in interior design, were investigated. For this pupose, these wood materials were cut superficially and radially according to the intersection directions, then the sample surfaces were varnished with one and two component water-based varnishes that do not contain solvent-based resin. The sound absorption coefficients of the obtained samples were determined by the impedance tube method and the results were compared statistically. It has been investigated that the obtained results could be evaluated statistically within the frequency values, besides, different results could be obtained according to the characteristics of natural wood materials, the direction of intersection and water-based varnish types. According to the findings obtained as a result of the study, it has been suggested that if natural wood material is used indoors, the superficial cross-section of East beech wood should be used according to the direction of intersection, and a two-component varnish should be used according to the varnish type.